2019
DOI: 10.17509/ijal.v8i3.15263
|View full text |Cite
|
Sign up to set email alerts
|

A ‘disjunct’ in the linguistic landscape: Messages about food and nutrition in Indonesian school environments

Abstract: In Indonesia’s schoolscapes, messages regarding food and nutrition abound. The researchers conducted descriptive, evaluative research on the nature and scope of the linguistic landscape around 20 primary school grounds in Jakarta and Depok education districts. The purpose of this study was to gather (digitally) and analyze food/nutrition signs/texts in order to determine which languages are represented in which places, and the kinds of messages for each language. As well, the study explored other non-food imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…These patterns were arranged from greatest to least frequent. LL study about Messages in food and nutrition in Indonesian school environments by Harbon & Halimi (2019) aimed at gathering (digitally) and analyzing food/nutrition signs/texts. The study found that Indonesian is the majority language in the texts and images, while Sundanese, Arabic, Japanese and English (monolingual) are in small percentages.…”
Section: Previous Studies On Linguistic Schoolscapesmentioning
confidence: 99%
See 1 more Smart Citation
“…These patterns were arranged from greatest to least frequent. LL study about Messages in food and nutrition in Indonesian school environments by Harbon & Halimi (2019) aimed at gathering (digitally) and analyzing food/nutrition signs/texts. The study found that Indonesian is the majority language in the texts and images, while Sundanese, Arabic, Japanese and English (monolingual) are in small percentages.…”
Section: Previous Studies On Linguistic Schoolscapesmentioning
confidence: 99%
“…Bates (2021) looked into the varying uses of languages on signs within a multicultural university setting in Tokyo, Japan. Food nutrition signs and texts were gathered (digitally) and examined by Harbon and Halimi (2019) to determine which languages were used where and what kinds of messages were conveyed in each language. Muriungi & Mudogo (2021) questioned the language distribution of public signage in the multilingual context in Kenyan universities and the students' attitudes towards public signs.…”
Section: Introductionmentioning
confidence: 99%
“…Monolingual frequency in Bahasa Indonesia is very dominant compared to English and Javanese. Ardiyanti [4], Harbon and Halimi [27] stated that the application of the Bahasa Indonesia as the official language indicates that it is easy to understand.…”
Section: Monolingual Signs In Ll School Scapementioning
confidence: 99%
“…It was also carried out in multilingual cities such as in Lita, Uganda [16], Rome [17], Bangkok [2], and Tokyo [3], Kuala Lumpur [18,19], Dilli, Timor Leste [20], Singapore [21,22] and Bangkok, Thailand [23]. LL studies were further examined city setting in Indonesia carried out by [4,[24][25][26][27][28][29]. Only two study conducted in Indonesia that focus on school sign, that is [4] and [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation